2021
DOI: 10.3390/children8010049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linear and Nonlinear Pedagogy Physical Education Interventions on Children’s Physical Activity: A Cluster Randomized Controlled Trial (SAMPLE-PE)

Abstract: Background: School-based interventions are a key opportunity to improve children’s physical activity (PA); however, there is lack of evidence about how pedagogical approaches to motor learning in physical education (PE) might affect PA in children. Therefore, this study aimed to assess how different pedagogical approaches in PE might affect children’s PA. Methods: Participants (n = 360, 5–6 years) from 12 primary schools within the SAMPLE-PE randomized controlled trial were randomly allocated to either Linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Pedagogic Fidelity scores were reported in Table 2 . Nonlinear pedagogy average intervention fidelity scores ranged from 3.95 (SD = 0.78) to 5 (SD = 0.00), Linear pedagogy intervention average fidelity scores were all lower than 1.77 (0.94), while control group average scores were comprised between 1.44 (SD = 0.97) and 2.50 (SD = 0.54) [ 71 ]. Fidelity scores of 1 and 2 on the Likert scale correspond to the observation being more in line with Linear pedagogy and scores of 4 and 5 correspond to the observation being in line with Nonlinear pedagogy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pedagogic Fidelity scores were reported in Table 2 . Nonlinear pedagogy average intervention fidelity scores ranged from 3.95 (SD = 0.78) to 5 (SD = 0.00), Linear pedagogy intervention average fidelity scores were all lower than 1.77 (0.94), while control group average scores were comprised between 1.44 (SD = 0.97) and 2.50 (SD = 0.54) [ 71 ]. Fidelity scores of 1 and 2 on the Likert scale correspond to the observation being more in line with Linear pedagogy and scores of 4 and 5 correspond to the observation being in line with Nonlinear pedagogy.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention fidelity in terms of Linear and Nonlinear pedagogy were independently assessed through the video analysis of recorded PE lessons using a checklist developed by the research team ( S4 Table ) [ 71 ]. The checklist comprised 9 items including 7 motor learning related items and 2 global items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 articles, the effect on physical fitness was analyzed. All of them were divided depending on the intervention main ideas: intensive interval training, [25][26][27] jumping and strength, 28,29 teaching styles, 14,30,31 and other. 18,32 On the other hand, 7 articles showed effect on both PA level and FMS.…”
Section: Interventions To Improve Ps Levels and Fmsmentioning
confidence: 99%
“…28 Regarding teaching styles, the studies showed positive effects in PA level in 2 studies, 14,31 but did not in another one. 30 A community-based approach in schools has shown positive effects. 4,13 Finally, involving students in activities with greater cognitive function have shown positive effects to improve FMS.…”
Section: Interventions To Improve Ps Levels and Fmsmentioning
confidence: 99%